The Effect of Leadership, Education and Communication Channel Factors on Patient Safety Culture - Tina Rahmawati; Arif Satria; Ninuk Purnaningsih (School of Business, IPB University (SB-IPB), 2018)
Organizational culture has an important role in improving patient safety. In order to improve the implementation of patient safety culture, management and organization culture need to be tranformed. The objectives of this study were to analyze patient safety culture among groups of units of the hospital and to analyze leadership, education, and communication channel related to patient safety culture. This study was based on surveys and data from Quota Random Sampling Method. The data processing for mean analysis of patient safety culture scores among groups of work units was conducted using ANOVA test while the analysis for the relationship of leadership, education, and communication channel with the patient safety culture was performed by using SEM Partial Least Square (PLS) application. The results show that safety patient culture has no significant differences among nursing work unit meanwhile, leadership and education give significant relations on patient safety culture, and communication channel has no significant relations. The patient safety culture that is evenly distributed among the nursing units is a strength for the organization, and the factors that influence the establishment of the patient safety culture on the nurses are leadership and education.Keywords: patient safety culture, leadership, education, communication channel